Sacubitril-Valsartan Increases Ultrafiltration in Patients Undergoing Peritoneal Dialysis: A Short-Term Retrospective Self-Controlled Study - Zhang, Fen; Zhang, Tingting; Yang, Sisi; Wang, Di; Zhuo, Qianqian; Qin, Xianhui; Gong, Nirong; Ai, Jun (Frontiers in Medicine, 2022)
Aim: There are few data about the effectiveness and safety of angiotensin receptor-neprilysin inhibitor (ARNI) sacubitril-valsartan in end-stage renal disease (ESRD) patients undergoing peritoneal dialysis (PD). The present study was conducted to evaluate the association between sacubitril-valsartan treatment and peritoneal ultrafiltration (PUF) in PD patients. Methods and Results: Forty-seven ESRD patients undergoing PD for at least 3 months without severe congestive heart failure (CHF) were included in this study. Sacubitril-valsartan (generally 100 mg b.i.d) was administered after consultation with the nephrologist. Angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs) were required to be discontinued 36 hours before prescribing sacubitril-valsartan. Other treatments and dialysis modality did not change. Baseline demographic and clinical parameters were collected before ARNI administration, and daily PUF, urine volume, total output, blood pressure (BP), and body weight were collected within 7 days before and after ARNI treatment. After treated with sacubitril-valsartan, 30 patients (63.8%) had a significant increase of PUF [up to 150.4 (110.7, 232.1) ml per day], while the remaining 17 (36.2%) had a slight decrease. The overall increase of PUF was 66.4 (21.4, 123.2) ml/24h within the 7 days after sacubitril-valsartan administration, which was significantly higher than those before (P = 0.004). Total output, BP, and body weight also significantly improved. No adverse drug reactions were observed. Conclusions: Our study indicated that sacubitril-valsartan was associated with the increase of short-term PUF and total output in PD patients.